The Development of Physical Activities Based on Racket Striking for Early Childhood Education Students in Yogyakarta City - Hidayat, Afif Khoirul; Susilowati, Sri; Suartini, Desk Ayu; Hastina, Sri; Santoso, Rahmawan; Aziz, Zainul; Yambedoan, Thadius (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This research aims to develop physical activities based on racket striking that are suitable for early childhood education children in Yogyakarta City. The research method employed is a simplified version of the Research & Development (R&D) model, which condenses the original ten stages into four main phases: Information Gathering, Development of Preliminary Product Form and Validation, Operational Field Testing, and Final Product Revision. The research subjects consisted of 64 ECE students from four schools in Yogyakarta City, selected using a proportional total sampling technique. The data analysis methods used were the Aiken V test and Dependent t-test. The research findings indicate that physical activities based on racket striking have an Aiken V value of 0.83, which signifies high validity. In the Operational Field Testing, it was found that the effectiveness of physical activities based on racket striking had a dependent t-test significance value of 0.00; thus it can be concluded that the physical activities based on racket striking can be used as a practical learning material to support the motor development of young children while considering safety aspects and its alignment with the developmental stages of children